Analisis User Experience Aplikasi SIMUNIPA Menggunakan Metode System Usability Scale : User Experience Analysis of SIMUNIPA Application Using System Usability Scale Method - Rizi Irama; Nur Arlin Hidayah; Dwi Nuhr Indriani; Josua Josen A. Limbong (Universitas Papua, 2025)
This study aims to evaluate the usability level of SIMUNIPA (University of Papua Information System) web application based on user experience using the System Usability Scale (SUS) method. The evaluation was conducted using 60 respondents consisting of students and alumni of the Informatics Engineering Department. The research method used is a descriptive quantitative approach by distributing SUS questionnaires online and offline. The evaluation results show an average SUS score of 76.66 which is in the “Good” and Acceptable High category. This finding shows that in general the SIMUNIPA application is easy to use and provides a fairly good user experience. However, there are still some problems such as unclear navigation, inconsistent interface display, and system response speed. The questionnaire instrument has gone through validity and reliability tests with valid and reliable results. Recommendations were given for system improvement, including the addition of usage guides, improvement of navigation structure, and optimization of system performance.